Reduction of torsional vibrations due to electromechanical interaction in aircraft systems - Ahumada Sanhueza, Constanza (2018)
With the growth of electrical power onboard aircraft, the interaction between the electrical systems and the engine will become significant. Moreover, since the drivetrain has a flexible shaft, higher load connections can excite torsional vibrations on the aircraft drivetrain. These vibrations can break the shaft if the torque induced is higher than the designed value, or reduce its lifespan if the excitation is constant. To avoid these problems, the electromechanical interaction between the electrical power system and the drivetrain must be evaluated. Past studies have identified the electromechanical interaction and introduced experimental setups that allow its study. However, strategies to reduce the excitation of the torsional vibrations have not been presented. This thesis aims to analyse the electromechanical interaction in aircraft systems and develop an advanced electrical power management system (PMS) to mitigate its effects. The PMS introduces strategies based on the load timing requirements, which are built on the open loop Posicast compensator. The strategies referred as Single Level Multi-edge Switching Loads (SLME), Multilevel Loading (MLL), and Multi-load Single Level Multi-edge Switching Loads (MSLME) are applied to different loads, such as pulsating loads, ice protection system, and time-critical loads, such as the control surfaces. The Posicast based strategies, eliminate the torsional vibrations after a switching event, by the addition of zeros that cancel the poles of the system. For this reason, the knowledge of the natural frequencies of the mechanical system is necessary. Experimentally, the system parameters are obtained through Fourier analysis of the step response and the strategies are applied. A robust analysis of the strategies allows the establishment of the range of uncertainty on the frequencies that allow the proper operation of the strategies. Simulation and experimental results show that the torsional vibrations can be reduced to values close to zero by the application of the strategy. Therefore, the PMS mitigates the electromechanical interaction between the electrical power system and the aircraft drivetrain.